Determination of electrical properties of physiological systems with digital techniques - Valdiosera, R. (Revista Mexicana de Ingenieria Biomedica, 1991)
Numerous physiological processes of cells and tissues are carried out by electrical events. The electrical activity takes place in the transduction of signals from the environment into nerve impulses, in the transmission of these impulses throughout the nervous system, in the contraction of the skeletal muscle and smoothness in the generation, conduction and propagation of the impulse in the muscle. cardiac and in the passage of liquids and solutes through the biological membranes. This bioelectric activity is developed with the participation of plasmatic membranes, through its structural and physicochemical properties.